The development of a scale for the measurement of the perceived importance of the dimensions of apparel store image - Janse van Noordwyk, H. S. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Consumer Science. Clothing and Textiles))--University of Stellenbosch, 2008.